2021
DOI: 10.4314/rejhs.v9i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Perception of facility readiness and health worker willingness to participate in the COVID-19 pandemic response in a treatment centre in Nigeria

Abstract: Objectives: The study aimed to investigate health workers’ knowledge, self - preparedness and willingness to volunteer for outbreak response and perceived institutional readiness to manage confirmed or suspected cases of COVID-19.Methods: Across-sectional study was carried out among 300 consenting healthcare workers in a COVID19 treatment facility in Edo  state, Nigeria. Data were collected between April and May 2020 using selfadministered questionnaires. Analysis was done using  Statistical Package for Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…An overview cross-sectional study done among African countries and middle East countries to ascertain the acceptances, attitude, and belief relating to vaccines in general and the COVID-19 vaccine revealed that 666.81% of respondent would like to be vaccinated against COVID-19, while 33.19% refuse vaccination. Reasons for vaccine hesitancy includes: concerns regarding vaccine side effects, fear of getting sick from uptake of the vaccine, religious belief, and absence of accurate vaccine promotion news [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…An overview cross-sectional study done among African countries and middle East countries to ascertain the acceptances, attitude, and belief relating to vaccines in general and the COVID-19 vaccine revealed that 666.81% of respondent would like to be vaccinated against COVID-19, while 33.19% refuse vaccination. Reasons for vaccine hesitancy includes: concerns regarding vaccine side effects, fear of getting sick from uptake of the vaccine, religious belief, and absence of accurate vaccine promotion news [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%